Coupling Strategies for the Synthesis of Peptide-Oligonucleotide Conjugates for Patterned Synthetic Biomineralization - Joshua D. Carter; Thomas H. LaBean (Journal of Nucleic Acids)
This work describes preparation strategies for peptide-oligonucleotide conjugates that combine the self-assembling behavior of DNA oligonucleotides with the molecular recognition capabilities of peptides. The syntheses include a solution-phase fragment coupling reaction and a solid-phase fragment coupling strategy where the oligonucleotide has been immobilized on DEAE Sepharose. The yield of four coupling reagents is evaluated, two reagents in water, EDC (1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride) and DMTMM (4-(4,6-dimethoxy[1,3,5]triazin-2-yl)-4-methyl-morpholinium chloride), and two in dimethylformamide (DMF), PyBOP ((Benzotriazol-1-yloxy) tripyrrolidinophosphonium hexafluorophosphate) and HBTU (O-benzotriazole-N,N,N′,N′-tetramethyluronium hexafluorophosphate), while the oligonucleotide fragment is either in solution or immobilized on DEAE. These coupling strategies rely on an unprotected 5′ amino linker on the oligonucleotide reacting with the peptide C-terminus. The peptide, selected from a combinatorial library for its gold-binding behavior, was 12 amino acids long with an N-terminus acetyl cap. Formation of the conjugates was confirmed by gel electrophoresis and mass spectrometry while molecular recognition functionality of the peptide portion was verified using atomic force microscopy. Solution-phase yields were superior to their solid-phase counterparts. EDC resulted in the highest yield for both solution-phase (95%) and solid-phase strategies (24%), while the DMF-based reagents, PyBOP and HBTU, resulted in low yields with reduced recovery. All recoverable conjugates demonstrated gold nanoparticle templating capability.